ANALISIS PENERAPAN MANAJEMEN KEUANGAN TERHADAP ALOKASI APBD DESA GONDOSULI TAHUN 2021 - Nyla Farida Yulianingsih; Riki Dwi Saputro (JIMBIEN: JURNAL MAHASISWA MANAJEMEN, BISNIS, ENTREPRENEURSHIP, 2022)
Penelitian ini dilakukan dengan maksud dan tujuan untuk mengetahui data penggunaan dana keuangan di desa Gondosuli periode tahun 2021 – 2022. Penggunaan dana desa perlu terus dipantau dan dimonitor karena dana tersebut harus benar untuk kepentingan desa dan digunakan untuk pembangunan infrastruktur di desa Gondosuli, oleh karena itu perlu adanya pembukuan keuangan dan pengelolaan keuangan dalam mengatur penggunaan dana desa. Pembukuan keuangan desa dapat menjadi data dan bukti dana desa digunakan untuk apa saja, sedangkan pengelolaan keuangan desa bertujuan agar dana desa dapat dikelola dan digunakan dengan sebaik-baiknya Abstract The purpose of this research is to examine data on the use of financial funds in Gondosuli village for the period 2021. The use of village funds needs to be continuously monitored and monitored because these funds must be true for the benefit of the village and used for infrastructure development in Gondosuli village, therefore there is a need for financial accounting and financial management in regulating the use of village funds. Village financial bookkeeping can be data and evidence that village funds are used for anything, while village financial management has a goal so that village financial management can be carried out properly and correctly. This study uses a descriptive method with a quantitative approach and verification method, which is the result of research which is then analyzed and processed to draw conclusions. This research was conducted directly in the field and observed and took data samples from sources. The purpose of this study is to see the use of village finances whether financial management has been implemented in Gondosuli village. The results of this study indicate that the Gondosuli village government has implemented financial management in the implementation of the APBD in Gondosuli village, by implementing financial management, village funds can be used optimally for infrastructure and other development in Gondosuli village.